أدب المنفلوطي النثرى : خصائصه الفنية وتوظيفه في تعليم الأدب العربي للناطقين بغير العربية - عيسوي, محمود مرغني (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
This study has handled the prose literature of Al-Manfalouti, its characteristics and its usefulness in the field of teaching Arabic literature to non-native speakers. The researcher has discussed the life of Al-Manfalouti and the factors that enrich his artistic literary prose literature in "Egyptian articles, novel and prose." He was brilliant in writing articles as his fine style depends on sensation, imagination and his personal feelings which are reflected well in his novels and stories. He was not an imitating scholar but a naturally-talented one as evident in his prose writing. His talent is evident as well in the analyses which the researcher has conducted on all discussed articles, prose and novels. The researcher has equally handled the prose aspects of the investigated scholar and the attitude of some of his contemporary scholars towards his works. Some of them have criticized his works, particularly his prose whereas others have appreciated his literary works in terms of style, prose and position which he deserves according to the age in which he survived. The researcher has as well refuted the criticism against Al-Manfalouti'sworks.The researcher is of the opinion that Al-Manfalouti's prose literature is useful to enable students who are non-native speakers of Arabic to understand contemporary literature, and develop their styles and talents. The researcher has developed four practical models of "linguistic unit methods" of Al-Manfalouti's prose literature for this purpose. They contribute to the curricula of teaching Arabic to advanced non-native speakers and the teaching of Arabic literature.